Don’t Dampen the Laughter: Difficulties in Translating Comedies - Papa, Mirela; Lama, Irena (Richtmann Publishing, 2012)
The presence of humor in audiovisual text as it is by the dialectal variants, the cultural references etc., implies achallenge for the translator, and we need to admit, it is not an easy challenge. As long as more elements are characterizedculturally, more it becomes almost impossible for the translator to recreate the same comic effects on the original film, as thenew spectator of the metatext who may not share the cultural environment and the cultural baggage of the prototext. This articlewill analyse problems encountered in the translation of Italian comedies into the Albanian language. We will see concretely howthe dialectal variants, the referents of language, the different registers of speech used to create various shades of humor inaudiovisual texts are difficult for the translator as a mediator between two cultures.